Measurement of the e+e- → pp[bar] cross section in the energy range from 3.0 to 6.5 GeV - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
The e+e−→p¯p cross section and the proton magnetic form factor have been measured in the center-of-mass energy range from 3.0 to 6.5 GeV using the initial-state radiation technique with an undetected photon. This is the first measurement of the form factor at energies higher than 4.5 GeV. The analysis is based on 469 fb−1 of integrated luminosity collected with the BABAR detector at the PEP-II collider at e+e− center-of-mass energies near 10.6 GeV. The branching fractions for the decays J/ψ→p¯p and ψ(2S)→p¯p have also been measured.
Im Titel ist das Pluszeichen "+" und das Minuszeichen "-" hochgestellt
Im Titel steht der zweite Buchstabe "p" mit einem Oberstrich
Gesehen am 15.11.2021